Coaches’ Perspectives about the Reasons behind Dropping Out of Sports in Wrestlers - Ömer Kaynar (Journal of Educational Issues, 2024)
It has been known that amateur or professional athletes quit competing because of personal and socio-economic reasons such as lack of financial, technical, or family support, and lack of motivation for a future career. Especially, it has been common in Turkish wrestling that many elite wrestlers quit competing at an early age. This research aims to determine the reasons why wrestlers quit the sport, according to coaches. A qualitative research method was used to conduct the study. The research population included 293 volunteer coaches who were active in sports clubs in fifty-one different cities in Turkey. Participating coaches consist of different experience levels, from beginner coaches to elite-level national head coaches. While descriptive statistics was used to determine the characteristics of the participants, the data was done through content analysis. The research data were obtained with four open-ended questions that were asked of the coaches. After the interview, the opinions of the coaches were written down based on the answers given to the questions. In this study, an example of the question, “Did any of your athletes quit wrestling?” was asked of 293 wrestling coaches. When the coaches were asked, “If your answer is yes, why do you think your athletes quit wrestling?” 173 (59.04%) out of 293 coaches stated that they quit wrestling due to future anxiety, 70 (23.89%) family, 30 (10.23%) disability, 17(5.80%) the coach, and 3(1.02%) friends. According to coaches, the main reason that wrestlers drop out of the sport is the concern about the future.